Natural language processing for automatically creating radiological reports - Lim, Hermes HongJun (Nanyang Technological University, 2024)
Radiologists examine Computerised Tomography (CT) and Magnetic Resonance Imaging (MRI) scans to synthesise radiology reports. The process involves manual scrutiny of the scans and although TTS software is available, dictating them is strenuous. Additionally, the radiology reports produced may be subjective depending on the radiologist’s findings. By leveraging existing computer vision models that offer segmentation results for brain volume, we can utilise them to enhance radiological reports by incorporating objective quantification of lesion volumes of the brain.